Influence of Serum Ferritin and B12 Levels in the Functional Outcomes of Patients with Ruptured and Unruptured Intracranial Aneurysms - Rabelo, Nícollas Nunes; Coelho, Antônio Carlos Samaia da Silva; Pipek, Leonardo Zumerkorn; Telles, Joao Paulo Mota; Barbato, Natalia Camargo; Yoshikawa, Marcia Harumy; Barbosa, Guilherme Bitencourt; Teixeira, Manoel Jacobsen; Figueiredo, Eberval Gadelha (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Introduction Pathological processes in the arterial wall that result in vessel dilation are the cause of intracranial aneurysms (IAs), and the risk factors for their formation and progression are not well established. Ferritin is associated with inflammation and angiogenesis; it has protective antioxidative activity, and controls cell differentiation. Vitamin B12 is related to neurological and hematological disorders; it can be used as differential diagnosis tool, and acts in the control of homocysteinemia, a predictor of worse prognosis. The present article aims to assess the correlation between serum ferritin and B12 levels and the patient's functional outcome.Materials and Methods In the present cohort study, we assessed the serum levels of ferritin and B12, as well as the scores on the modified Rankin and Glasgow Outcome Scales at 6 months, of 2 groups, one with 19 and the other with 49 individuals, out of 401 patients treated for IA at Universidade de São Paulo from 2018 to 2019. We performed a statistical analysis, using logistic regression, to determine the aforementioned correlation.Results In the univariable analysis, the serum levels of ferritin showed no significant impact on the functional outcome (odds ratio [OR]: 0.96 for every 100 pg/mL increase; 95% confidence interval [95%CI]: 0.761–1.210; p = 0.732); neither did the serum levels of B12 (OR: 0.998 for every 100 pg/mL increase; 95%CI: 0.826–1.206; p = 0.987). Moreover, no significant impact on the functional outcome was observed in the multivariable analysis regarding the serum levels of B12, age, hypertension, and aneurysm rupture (OR: 1.086 for every 100 pg/mL increase; 95%CI: 0.847–1.392; p = 0.513).Conclusion We were not able to confirm a statistical correlation regarding the serum levels of ferritin and B12, and functional outcome of IA patients. These variables might be linked to other determinants of the pathophysiology of IAs, like inflammation and homocysteinemia.
Keywords: brain aneurysm; ruptured intracranial aneurysm; unruptured intracranial aneurysm; subarachnoid hemorrhage; serum ferritin; serum B12